Dispersion of powders in liquids and stabilization of suspensions - Tadros, Tharwat F (Wiley-VCH, 2012)
Teaching the fundamental knowledge required for successful dispersion of powders in a liquid, this book covers a host of topics -- from recent advances to industrial applications. In 15 chapters it supports formulation chemists in preparing a suspension in a more rational way, by applying the principles of colloid and interface science, while at the same time enabling the research scientist to discover new methods for preparing stable suspensions. Essential reading for those working in the pharmaceutical, cosmetic, food, paint, ceramic and agricultural industries.